Glofitamab treatment of Richter transformation with isolated central nervous system involvement: a case report - Lu, Kang; Chen, Ping; Zhang, Xiaohui; Zheng, Weicheng; Zhang, Liying; Wu, Xuemei; Li, Bingzong (Frontiers in Immunology, 2025)
Diffuse large B-cell lymphoma (DLBCL) is a common subtype of Richter transformation (RT) in chronic lymphocytic leukaemia (CLL), accounting for 90–95% of all transformation cases. However, RT with isolated cerebral involvement is rare. Herein, we report the case of a 67-year-old man with DLBCL that transformed from CLL during obinutuzumab treatment. This patient developed RT with only central nervous system (CNS) involvement and no systemic features. After undergoing single-agent treatment with the CD20×CD3 bispecific antibody glofitamab, the patient regained consciousness and improved clinically. Although only one successful case has been presented, glofitamab may be considered a promising therapeutic option for patients with RT and isolated CNS involvement.